Improved post-ASCT survival of relapsed/refractory classical Hodgkin lymphoma patients in the era of novel agents. Issue 4 (21st March 2022) - Shah, Harsh; Jang, Hyejeong; Singh, Paramveer; Kosti, Jorgena; Kin, Andrew; Alavi, Asif; Ratanatharathorn, Voravit; Ayash, Lois; Uberti, Joseph; Ramchandren, Radhakrishnan; Kim, Seongho; Deol, Abhinav
Abstract: Utilization of novel agents such as brentuximab vedotin (BV) and check-point inhibitors (CI) has increased in patients with relapsed/refractory (r/r) classical Hodgkin Lymphoma (cHL). We conducted a retrospective study of 209 patients who had ASCT for r/r cHL at our institution and compared outcomes of those who had ASCT from 2010–2018 (cohort 2, n = 110) with those who had ASCT between 2000 and 2009 (cohort 1, n = 99). The median OS was 7.6 years for cohort 1 [HR 2.08; 95% CI 1.14–3.80; p = 0.017] and not reached for cohort 2; with 4-year improved OS difference of 15% (80% vs 65%) in cohort 2 vs cohort 1. The median PFS of cohort 1 was 30 months vs 39 months for cohort 2[HR 1.24; 95% CI 0.82–1.88; p = 0.3]. This study highlights improved OS of r/r cHL patients who have received ASCT in the novel agent era due to the exposure to agents such as BV and CIs.